Dynamics and its Effects on Saturation Region in Semiconductor Optical Amplifiers - Mohammed, Adnan H.; Jassem, Muna M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
We focus on studying the dynamics of bulk semiconductor optical amplifiers and their effects on the saturation region for short pulse that differ, however there is the same unsaturated gain for both dynamics. Parameters like current injection, fast dynamics present by carrier heating (CH), and spectra hole burning (SHB) are studied for regions that occur a response to certain dynamics. The behavior of the saturation region is found to be responsible for phenomena such as recovery time and chirp for the pulse under study.